GPS Tracker Through HF Radio Using FSK Method - Homam, M J; Khazali, M F M; Kamaruddin, S (International Journal of Engineering and Technology, 2018)
A GPS tracker through HF radio using FSK method for Blue Force Tracking (BFT) application was developed. The project aims to transmit and receive the location information which is obtained from the GPS data. The system used frequency range of 500 Hz to 2000Â Hz for modulating and demodulating the GPS data using FSK method. The smallest frequency gap between characters without affecting the accuracy of the output is 100 Hz, but the transmission time per character must be set to 100 ms. The transmission speed was investigated to find the optimum speed of the system by varying the delay command in the program. The system can accurately transmit and receive the location data in 1350 ms per coordinate. In general, the developed system successfully maintains the performance of transmitting and receiving the location information which can be applied for the future advancement of the BFT.